Internalizing the Values of Islamic Education in the Learning of Physics in MA Darul Ulum Purwogondo - Muhamad Abi Ya’sub (Tarbiyah Departement collaboration with AMCA, 2021)
This study aims to determine the process of learning Physics that runs in MA Darul Ulum Purwogondo and the process of internalization of the values of Islamic education in the subjects of Physics. The results showed that of the materials that are taught in the learning of Physics, there are some material relation to the Islamic education such as the theory of relativity where the theory is related to the events of isra’ mi'raj the Prophet Muhammad which relate to the speed of light is the highest speed in this universe, no one can compete except the will and power of Allah SWT. The efforts made by the Physics teacher in the internalise the values of Islamic education in subjects of Physics in MA Darul Ulum Purwogondo include: 1) Implementing the learning methods which vary according to the material being taught, 2) Instill the value of- the value of Islamic education by being role models of good, 3) Undertake the development of the subject matter of Physics with the way of the development of the syllabus, 4) Gives understanding to students about the internalization of the values of Islamic education in materials Physics in depth based on the Al-qu'ran and the Hadith, and 5) Be a teacher who is nurturing students with the approach of the individual can also become a friend.